Fractionalization of Majorana-Ising-type quasiparticle excitations - Sanches, J. E. [UNESP]; Lustosa, L. T. [UNESP]; Ricco, L. S.; Shelykh, I. A.; De Souza, M. [UNESP]; Figueira, M. S.; Seridonio, A. C. [UNESP] (American Physical Society (APS), 2023)
We theoretically investigate the spectral properties of a quantum impurity (QI) hosting the here proposed Majorana-Ising-type quasiparticle excitation. It arises from the coupling between a finite topological superconductor (TSC) based on a chain of magnetic adatoms-superconducting hybrid system and an integer large spin S flanking the QI. It is noteworthy that the spin S couples to the QI via the Ising-type exchange interaction. As the Majorana zero modes (MZMs) at the edges of the TSC chain are overlapped, we counterintuitively find a regime wherein the Ising term modulates the localization of a fractionalized and resonant MZM at the QI site. Interestingly enough, the fermionic nature of this state is revealed as purely of the electron tunneling type and, most astonishingly, it has the Andreev conductance completely null in its birth. Therefore, we find that a resonant edge state appears as a zero mode and discuss it in terms of a poor man's Majorana [Dvir, Nature 614, 445 (2023)0028-083610.1038/s41586-022-05585-1].